2019
DOI: 10.1101/813550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miRViz: a novel webserver application to visualize and interpret microRNA datasets

Abstract: AbstractMicroRNAs (miRNAs) are small non-coding RNAs that are involved in the regulation of major pathways in eukaryotic cells through repression of their target genes at the post-transcriptional level1. While high-throughput approaches are broadly used to decipher the biological relevance of miRNAs, extraction of significant information from large miRNA datasets remains challenging. For example, sequencing technologies can quantify the relative expression … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…MiR-139-5p, that we have previously described as a marker of tumor aggressiveness, 25,26 was markedly repressed following silencing of β-Catenin, while miR-483-5p, a marker of malignancy, was not affected. Analysis of the genomic position of β-Cateninregulated miRNAs using miRViz software 39 revealed that many of them were localized in the same genomic region (Figure 2b), namely the 14q32 locus that we and others have previously identified as particularly deregulated in ACC. 8,25 Among the miRNAs that we found affected by β-Catenin silencing, we selected 8 of them for RT-qPCR validation, based on their p-value for prognosis (Supplementary Figure S3), including 4 miRNAs of the 14q32 locus (miR-377-5p, miR-377-3p, miR-1185-2-3p and miR-541-3p), miR-139-5p (chr 11), miR-320b (chr 1), miR-2110 (chr 10), and miR-513a-5p (chr X).…”
Section: Inactivation Of Wnt/β-catenin Signaling Affects Microrna Exp...mentioning
confidence: 87%
“…MiR-139-5p, that we have previously described as a marker of tumor aggressiveness, 25,26 was markedly repressed following silencing of β-Catenin, while miR-483-5p, a marker of malignancy, was not affected. Analysis of the genomic position of β-Cateninregulated miRNAs using miRViz software 39 revealed that many of them were localized in the same genomic region (Figure 2b), namely the 14q32 locus that we and others have previously identified as particularly deregulated in ACC. 8,25 Among the miRNAs that we found affected by β-Catenin silencing, we selected 8 of them for RT-qPCR validation, based on their p-value for prognosis (Supplementary Figure S3), including 4 miRNAs of the 14q32 locus (miR-377-5p, miR-377-3p, miR-1185-2-3p and miR-541-3p), miR-139-5p (chr 11), miR-320b (chr 1), miR-2110 (chr 10), and miR-513a-5p (chr X).…”
Section: Inactivation Of Wnt/β-catenin Signaling Affects Microrna Exp...mentioning
confidence: 87%
“…From the predicted and validated targets, using expression data and/or sequencing information, more systemic analysis tools were developed to model the mutual influence of miRNAs on genes and pathways [110]. For example, the program miRTarVis [111] displays coexpression networks of paired miRNA and mRNA data, MIENTURNET [112] generates interaction networks of miRNA and mRNA with enrichment analysis, miRViz [113] visualizes networks for multiple species, miRNet [114] supports statistical analysis and facilitates exploration of miRNA-target interaction networks, miTALOS [115] analyzes miRNA function in a tissue-specific manner, and miRTrail [116] analyzes miRNA and gene expression data in an integrated manner. To increase the specificity of target predictions a priori, available information from pathway databases can be used.…”
Section: Open Accessmentioning
confidence: 99%
“…To this end, several analytical tools and bioinformatic databases have been developed. In the case of miRNAs, several research tools with varying scope and functionality were developed, including: MIENTURNET [45], miRNet [46] and miRViz [47], which generate miRNA-target interaction networks; miRTarVis [48] that can be used to visualize co-expression networks of paired miRNA and mRNA data; miRUPnet [49], miEAA [50], BUFET [51] and miSEA [52], which are databases providing enrichment analysis for miRNAs; the online database miRNApath [53] and the R package CORNA [54], which incorporate GO and KEGG enrichments obtained from predicted and validated miRNA-target interactions; miRTar [55], a tool that links individual miRNAs to metabolic pathways; miTALOS v2 [56], a program that has been developed to analyze miRNA functions and tissue-specific regulation in signaling pathways; DIANA-mirPath v3.0 [57], a web server used for miRNA pathway analysis that can be used to predict miRNA targets through the DIANA-microT-CDS algorithm; miRPathDB 2.0 [58], which indexes enriched pathways for known miRNAs and miRNA candidate genes using validated and predicted target genes from the literature; miRTargetLink 2.0 [59], an interactive tool for miRNA research that dynamically presents miRNA target genes and pathway networks; miRPathDB 2.0 [58] and miRTargetLink 2.0 [59], two recently published databases for which the pathway information supports interpretability and which focus on miRNA pathways, somehow limiting their scope. As for tools available for lncRNA analysis, those with an application scope closest to the redesigned NcPath proposed here include: NONCODE [60], LNCipedia [61] and RNAdb [62], which are comprehensive databases that provide basic annotation information for lncRNAs; Co-LncRNA [63], Lnc-GFP [64], LncTarD [65], LncR2metasta [66] and FARNA [67], which were developed to infer lncRNA biological functions; NPInter [68], lnCeDB [69], starBase v2.0 [70], DIANA-LncBase [71], miRSponge [72] and PceRBase [73], which provide information on lncRNA-target relationships.…”
Section: Introductionmentioning
confidence: 99%